In vitro culture of epithelial autografts for treating skin ailments - Calvo-Castro, Laura A. (2015)
Worldwide, novel therapeutic strategies have allowed an improvement on the attention and recovery of several skin ailments. However, to date in Costa Rica, there is no treatment, as a current routine protocol, to allow more effective and permanent re-epithelization of patients with chronic or large wounds on the skin. Given the existence of a national program for the production and transplant of skin cells, many patients with skin affections could be treated in the country, with less traumatic and more effective rehabilitation, and with lesser hospital stays. One option to solve this problem, is the in vitro culture of skin cells (fibroblasts and keratinocytes) for the production of autologous dermo-epithelial equivalents for grafting, a procedure currently available at the Tissue Engineering Laboratory (LAINTEC) of the Biotechnology Research Center at the Costa Rica Institute of Technology (ITCR).